A Study of the Ethical Approach of Maternal Thinking with Emphasis on the Ruddick s Perspective and Inference of Its Implications in Education. - Maryam Ghafarzadeh; Mohammad Hasan Mirza Mohammadi; Akbar Rahnama; Masud Safaei Moghadam (Shahid Chamran University of Ahvaz, 2022)
Sarah Roddick, a feminist ethicist, proposed the maternal thinking approach. Based on this approach, the maternal voice can be heard. Roudick's analysis showed a strong link between care ethics and maternal ethics. Roudick's philosophical work laid the groundwork for raising children from a feminist perspective of peace. In his view, mothers' actions are respected as peace. However, mothers do not have a pre-prepared model for performing maternal actions and their care is accompanied by compassion and love. For many men and women, the maternal model can be a symbol of care and shape the experience and work of caring. In the relationship between mother and child, ethics Care largely goes beyond analysis and reasoning and is related to maternal activities. As a provider of motherly thinking, Ruddick emphasizes that motherly action involves different ways of thinking and acting.In order to achieve the goals of the research, analytical (conceptual) and inferential methods were used appropriately. In order to answer the second question of the research, from the deductive inferential approach to the inference of educational meanings.Data analysis showed that in education based on loving and motherly thinking; The general goal of education is "peace education". In this approach, the teacher has characteristics such as: love, reflection, the ability to wait, attention, awareness, moderation and humility. The capabilities are unlimited. The educational environment should also be an environment with security, vitality and freshness. The motherly thinking approach has the potential to be considered as a model in social and educational relationships.Accordingly, first, the maternal thinking approach was analyzed and its basic elements were examined. Maternal ontology is a kind of communication and experience is the basis of its epistemology in which thinking and action are necessary and necessary to each other. Maternal ethics is based on another preference on itself. Three goals are protection, growth and education (social acceptance). From the point of view of maternal thinking, mothers use the principle of love in performing caring roles. Attention love is protective love (maintenance love), Scrutiny Love ،love and humility.